(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article notes that the introduction of martial law in Ukraine has changed the approach to the organisation of police work, since domestic law enforcement agencies have faced challenges previously unknown to science and practice, in particular, in the area of prevention of administrative delinquency among internally displaced persons, in the de-occupied territories, and in the context of hostilities, which required new algorithms and approaches, as well as consideration of the priorities and principles of activity. It is emphasised that in order to ensure the widest possible consideration of the fundamental principles, including the rule of law, police activity should be based on a coherent and consistent system of indicators which is relevant to modern socio-political realities. An important indicator of police activity is the effectiveness of work in the area of prevention of administrative delinquency. Measurement and analysis of this indicator are rather complex processes, as they are carried out not only within the framework of police activities, but are also largely related to the functioning of civil society institutions, educative, cultural, scientific and educational institutions and organisations, including international ones, which focus their activities on solving urgent problems that constitute the social basis of administrative delinquency. It has been noted that prevention of administrative delinquency is a complex category which should be considered through the prism of a system of organically interrelated actors at the level of understanding a wide range of relations between them, including police bodies and units. It has been emphasised that such a system should be based on the principles of equality, broad public participation and be coordinated by collectively formed management centres at the level of the State or a particular area (region, community). The areas for further development of police activities in the field of prevention of administrative delinquency include a set of organisational and administrative measures related to the need to ensure the rights and freedoms of internally displaced persons, prevention of bullying under martial law, and widespread application of the programme approach both in administrative law and administrative law doctrine.